Celebrating Howard Watkins' 40th Birthday in Backyard - Watkins, Howard::::::::: (1987)
Cindy Kamptner, Greg Kamptner, Wes Merritt, Mary Merritt, Pamela Stone and John Slutter; in background: Cynthia Manzer and Tom Riggs